2017
DOI: 10.1210/en.2016-1629
|View full text |Cite
|
Sign up to set email alerts
|

BMP7 Induces Uterine Receptivity and Blastocyst Attachment

Abstract: In women, the window of implantation is limited to a brief 2- to 3-day period characterized by optimal levels of circulating ovarian hormones and a receptive endometrium. Although the window of implantation is assumed to occur 8 to 10 days after ovulation in women, molecular markers of endometrial receptivity are necessary to determine optimal timing prior to embryo transfer. Previous studies showed that members of the bone morphogenetic protein (BMP) family are expressed in the uterus necessary for female fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 42 publications
0
39
0
Order By: Relevance
“…BMPs play a vital role in bone and cartilage development. These proteins are involved in the TGF-β signaling pathway and in cytokine receptor interaction [ 69 ], and are one of the proteins that are responsible for endometrial receptivity, e.g., BMP-2 and BMP-7 [ 70 , 71 ]. TGF-β3 decreases human endometrium receptivity by decreasing the expression of BMP receptors [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…BMPs play a vital role in bone and cartilage development. These proteins are involved in the TGF-β signaling pathway and in cytokine receptor interaction [ 69 ], and are one of the proteins that are responsible for endometrial receptivity, e.g., BMP-2 and BMP-7 [ 70 , 71 ]. TGF-β3 decreases human endometrium receptivity by decreasing the expression of BMP receptors [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike BMP2, BMP7 reduces E2/P4-induced expression of IGFBP1 mRNA in human ESCs in culture, suggesting an inhibitory role of BMP7 in ESC decidualization [ 76 ]. This finding seems to contradict results from the mouse model in which loss of BMP7 affects decidual gene expression [ 52 ]. Expression analysis has shown that the levels of BMPR1A, BMPR1B and BMPR2 are lower in leiomyoma-associated endometrium that secretes high levels of TGFβ3 versus normal endometrium [ 77 ].…”
Section: Tgfb Superfamily Signaling Regulates Uterine Decidualizationmentioning
confidence: 78%
“…Loss of BMP2 in the uterus renders the mouse infertile and the uterus is unable to decidualize, owing to the dysregulation of multiple genes including Wnt4/6 , FK-506 binding proteins ( Fkbps ), and prostaglandin synthase2 ( Ptgs2 ) [ 41 ]. Recently, conditional deletion of Bmp7 induces implantation defects and dysregulation of decidual genes including Bmp2 , Ptgs2 , Wnt4 , and epiregulin ( Ereg ) [ 52 ]. However, Bmp7 cKO mice respond normally to artificial decidualization stimuli [ 52 ].…”
Section: Tgfb Superfamily Signaling Regulates Uterine Decidualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…BMP7 has also been shown to play significant roles in the development of various types of tissues, such as kidney and brown adipose tissue. In mice, BMP7 was involved in sertoli cell proliferation during early postnatal development, and BMP 7 gene knockout mice caused infertility ( Puglisi et al, 2004 ; Monsivais et al, 2017 ). BMP7 has also been shown to participate in embryogenesis, tissue growth, and neurogenesis ( Bragdon et al, 2011 ; Kowtharapu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%